Cryptococcal fungemia and Mycobacterium haemophilum cellulitis in a patient receiving ruxolitinib: a case report and literature review - Naruemit Sayabovorn (2022)
Background: Ruxolitinib is a novel oral Janus kinase inhibitor that is used for treatment of myeloproliferative diseases. It exhibits potent anti-inflammatory and immunosuppressive effects, and may increase the risk of opportunistic infections. Here, we report a rare case of Cryptococcus neoformans and Mycobacterium haemophilum coinfection in a myelofibrosis patient who was receiving ruxolitinib. Case presentation: A 70-year-old Thai man who was diagnosed with JAK2V617F-mutation-positive primary myelofibrosis had been treated with ruxolitinib for 4 years. He presented with cellulitis at his left leg for 1 week. Physical examination revealed fever, dyspnea, desaturation, and sign of inflammation on the left leg and ulcers on the right foot. Blood cultures showed positive for C. neoformans. He was prescribed intravenous amphotericin B deoxycholate with a subsequent switch to liposomal amphotericin B due to the development of acute kidney injury. He developed new onset of fever after 1 month of antifungal treatment, and the lesion on his left leg had worsened. Biopsy of that skin lesion was sent for mycobacterial culture, and the result showed M. haemophilum. He was treated with levofloxacin, ethambutol, and rifampicin; however, the patient eventually developed septic shock and expired. Conclusions: This is the first case of C. neoformans and M. haemophilum coinfection in a patient receiving ruxolitinib treatment. Although uncommon, clinicians should be aware of the potential for multiple opportunistic infections that may be caused by atypical pathogens in patients receiving ruxolitinib.